Prevalencia de conductas antisociales y delictivas en estudiantes nivel secundario Túpac Amaru II - Florencia de Mora - Acuache Luna, Kimberly Lisbeth (2018)
The antisocial and criminal behavior are a mental health problem prevalent, serious and expensive. This study has as main objective to determine the prevalence of antisocial and criminal behavior in secondary level students of the Tupac Amaru II- Florence of Mora school; in addition, compare them according to: grade, gender, age and family composition. It is a descriptive cross sectional study, where the sample was composed of 473 students, was used the questionnaire of antisocial - criminal conducts and statistical tests used were: Z of proportions and Chi-square test to compare the behaviors according to grade, gender and age. The prevalence obtained in antisocial behaviors (CA) and criminal (CD) were 43.1% and 36.8%, respectively. According to level; the highest prevalence in CA was in 3° and 5° degree (48.8%) and CD 3° degree (45.3%). Both behaviors have greater prevalence in the group of males; at the same time, adolescents of 17 years over single-parent and extended family. It was concluded that there is a high prevalence in the behaviors studied in students of the Tupac Amaru II school, at the secondary level